Principles of economics - Case, Karl E., 1946-2016; Fair, Ray C., 1942-; Oster, Sharon M., 1948- (Harlow : Pearson, 2025)
All-time bestselling Principles of Economics is trusted for its clear, thorough and complete coverage of how market economies function. Covering both macro- and microeconomics perspectives, it balances economic theory, institutional material and real-world examples, with emphasis on the art and science of economic thinking. The 14th Edition features streamlined chapters, revised problems and all-new macro data through 2023. It adds 23 new Economics in Practice boxes with recent research and analysis, such as the impact of the COVID-19 pandemic on supply chains. In MyLab, new Economics in Practice videos featuring Emily Oster make economics relevant and relatable, while equipping you for success.
Aktualizované globální vydání knihy představuje komplexní a dlouhodobě osvědčený úvod do ekonomické teorie. Autoři vyvažují mikroekonomické a makroekonomické pohledy, propojují teoretické koncepty s institucionálním kontextem a ilustrují je příklady z reálného světa. Čtrnácté vydání obsahuje zjednodušené kapitoly, upravené úlohy, aktuální makroekonomická data do roku 2023 a 23 nových případových studií, včetně analýz dopadů pandemie COVID-19 na dodavatelské řetězce. Digitální podpora MyLab nabízí také nová videa, která činí ekonomická témata přístupnější a praktičtější.
Obsahuje bibliografii a rejstřík
Keywords: ekonomie; makroekonomie; mikroekonomie; učebnice; případové studie; economics; macroeconomics; microeconomics; textbooks; case studies